Nutritional and range management practices for breeding beef females - Pacheco, Leopoldo Arturo IV (Kansas State University, 2013)
The objective of this series of studies was to develop and improve methods of production in cow/calf operations of the Great Plains. Ultrasound measures of longissimus muscle depth (LMD) and intramuscular fat (IMF) of Angus × heifers were used to predict lifetime cow productivity. IMF and LMD were categorized into high, medium, and low groups (IMFG and LMDG, respectively). Cows in the high and medium LMDG had greater (P < 0.05) pregnancy rates than cows in the low LMDG. Calf BW at weaning increased (P < 0.05) as dam IMF increased. Angus crossbred cows grazing native range were used to evaluate the effects of pre-partum ruminally-protected choline (RPC) supplementation on postpartum beef cow and calf performance. Under the conditions of our study, RPC supplementation had minimal (P > 0.05) effects on pregnancy rates and performance of beef cows and calves. Lactating crossbred cows with calves and non-pregnant, non-lactating Boer-cross nannies were used to evaluate the effects of co-grazing on herbivory patterns and animal performance while grazing native tallgrass rangeland infested heavily by sericea lespedeza (SL). The proportion of individual SL plants that had been grazed at the end of the trial was greater (P < 0.01) in co-grazed pastures than in single-species pastures. Grazing cows and goats in combination increased (P < 0.01) grazing pressure on SL without negatively affecting beef cow performance, beef calf performance, or residual forage biomass. Angus × cows and heifers grazing native range were used to evaluate the effects of pre-partum corn steep liquor supplementation on postpartum beef cow and calf performance. Under the conditions of our study, CSL supplementation did not generally promote beef cow and calf performance that was equivalent to supplementation with an isonitrogenous, dry, corn-soy alternative. Cow calf pairs were used to evaluate the effects of grazing system (GS) and stocking rate (SR) on cow and calf performance. Late season rest-rotation (LSRR) was compared with continuous (CONT) grazing at low, moderate, and high SR. Under the conditions of our study, CONT produced consistently better (P < 0.01) late-season cow and calf performance than LSRR. Season-long effects of SR on animal performance were minimal; moreover, GS and SR treatments produced equivalent pregnancy rates.
Keywords: Beef cows; Nutrition; Managment; Animal Sciences (0475)